Antiemetic Drug Use in Children: What the Clinician Needs to Know. Issue 4 (April 2019) - Romano, Claudio; Dipasquale, Valeria; Scarpignato, Carmelo
Abstract : ABSTRACT: Vomiting is not only unpleasant for both children and families, but can lead to frequent hospital admission. The persistent vomiting hampers oral intake and increases the risk of dehydration, so the proper use of antiemetic drugs can be useful. The pharmacological treatment of vomiting in children remains a challenge for the pediatrician because several antiemetics are prescribed as "off-label, " outside their authorized drug label. Domperidone and ondansetron are the most commonly known antiemetic drugs. A single oral dose of ondansetron has been shown to reduce the risk of recurrent vomiting, the need for intravenous fluids, and hospital admissions in children with acute gastroenteritis. There is enough evidence to support ondansetron administration in children, so the clinical use can be defined as "off-label/on evidence." This review aims to provide an overview of therapeutic use, safety, and main pharmacological properties of antiemetic drugs in children. A comprehensive search of published literature using the PubMed MEDLINE database was carried out to identify all articles published in English from 1998 to February 2018. At present time, the "off-label/on-evidence" use of some antiemetics could improve the success rate of oral rehydration therapy in pediatric emergency settings and to change the management of vomiting with the prevention of the complications. Abstract : Supplemental Digital Content is available in the text